The Microalgae of Aquaculture - Arnaud Muller-Feuga; Jeanne Moal; Raymond Kaas (Blackwell Publishing, 2025)
This chapter considers the biological features of microalgae most commonly used in hatcheries as well as their biochemical composition, paying special attention to those compounds beneficial to marine animal nutrition. Finally, microalgal production systems are described and compared with those implemented in hatcheries, particularly in economic terms.